Effectiveness of Antiviral Drugs as Covid-19 Therapy - Adelia Firandi; Didik Hasmono (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2021)
Introduction: SARS-CoV 2 firstly emerged in China on December 2019 and it was spreading rapidly across the world until now. At this time, there is no vaccine or medication approved by the FDA. However, there are some FDA approved medicines for treating other diseases that can be used for Covid-19 based on tests. This review focuses on therapy efficacy, work mechanism, pharmacokinetic profile, safety, and future perspective. Method: Article review related to therapy on Covid-19 patients, particularly antiviral therapy which was the combination of lopinavir and ritonavir, chloroquine, hydroxychloroquine, remdesivir, and favipiravir. The reviewed relevant articles were observational study, in vitro test, case report, and clinical test. Results: A total of 13 articles met the requirement, 9 articles discussed the result of therapy during the medication of COVID-19 patients, 2 reports of in vitro test, and 2 results of clinical trials. Conclusion: From several studies that had been conducted, remdesivir, combination of lopinavir and ritonavir, as well as favipiravir showed benefits in various clinical studies on Covid-19 patients. Meanwhile, chloroquine and hydroxychloroquine showed limited effects and did not affect the decrease of mortality.